Konstrukcijske lastnosti in uporaba celičnih gradiv: Skripta - Vesenjak, Matej (University of Maribor Press, 2017)
Structural Properties and Use of Cellular Materials. The script presents the basic types of cellular materials, the methods of fabrication and the possibilities of their applications in engineering and other fields. The structural properties of different types of cellular materials are described in a detail and compared to the mechanical and thermal properties of the base materials from which they are made of. Their advantages, disadvantages and limitations are outlined, as well as ideas and guidelines for their improvement. Particularly emphasized are the mechanical behaviour of cellular materials and the energy absorption capabilities. Existing literature in the field of cellular structures and the diverse possibilities of their applications are presented in a comprehensive way.